A hierarchical optimization strategy for position and thickness optimization of constrained layer damping/plate to minimize sound radiation power - Dongdong Zhang (Advances in Mechanical Engineering, 2018)
A hierarchical optimization strategy is proposed to optimally design constrained layer damping materials patched on the base plate for minimizing sound radiation power. A sound radiation optimization model is established by taking positions and thicknesses of constrained layer damping materials as design variables, and added mass as constraints. The hierarchical optimization procedure is implemented, in which evolutionary structural optimization method is employed to get optimal position layouts of constrained layer damping materials, and genetic algorithm is used to find optimal thickness configurations of constrained layer damping materials by taking the plate with optimal position layouts of constrained layer damping materials as initial structure. Two sound power sensitivities are formulated and compared for position optimization. Numerical examples in which unweighted/weighted objective functions are considered are presented, optimal positions and thickness configurations of constrained layer damping materials patched on the plate are obtained and discussed. The results demonstrate that the proposed strategy is very effective to achieve larger sound power reduction by reconfiguring the thickness of constrained layer damping materials for the results of position optimization.